2010
DOI: 10.1063/1.3460150
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of PbS quantum dots on semi-insulating GaAs

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Department of Defense, Washington Headquarters Services, Directorate for Informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 15 publications
5
17
2
Order By: Relevance
“…The thickness of the film can be varied by changing the concentrations or the volume of the nanoparticle solution. The surface morphology of these films is comparable to the PbS QD arrays achieved by a sc-CO 2 fluid deposition process (Smetana et al 2008;Wang et al 2010) including those reported on a GaAs substrate (Ullrich et al 2010). In general, the images of the Au and PbS NP films deposited by the CDM procedure reveal fairly homogenous coverage on different substrates.…”
Section: Deposition Of Au and Pbs Nps Using Cdm Methodssupporting
confidence: 53%
“…The thickness of the film can be varied by changing the concentrations or the volume of the nanoparticle solution. The surface morphology of these films is comparable to the PbS QD arrays achieved by a sc-CO 2 fluid deposition process (Smetana et al 2008;Wang et al 2010) including those reported on a GaAs substrate (Ullrich et al 2010). In general, the images of the Au and PbS NP films deposited by the CDM procedure reveal fairly homogenous coverage on different substrates.…”
Section: Deposition Of Au and Pbs Nps Using Cdm Methodssupporting
confidence: 53%
“…5,24 The fit result for θ D is substantially smaller than the value of 145 K in bulk PbS obtained from x-ray Bragg reflection. 25 Other reports provide values in the range of 75-300 K. 26,27 It should be mentioned that other samples prepared with different annealing conditions also show low θ D values but reach maximum values of up to 82 K.…”
Section: A Characterization By Absorption and Ss-pl Spectramentioning
confidence: 92%
“…A PL peak of about 430 nm is associated with the transition of electrons from the conduction band edge to holes trapped in interstitial Pb 2+ sites. The PL intensity is much higher for PbS films than for the Si(1 0 0) substrate because the temperature of the carrier in the latter case increases [17]. Figure 7(b) shows the PL spectra of PbS film deposited at t = 2 h and at 25, 45 and 65°C and an excitation wavelength of 335 nm.…”
Section: Photoluminescencementioning
confidence: 94%
“…A variety of approaches have been proposed for silicon-based light-emitting structures. The quantum confinement of carriers in nanostructured silicon systems and deposition of semiconductor NCs on a Si substrate are interesting research areas [16,17,29]. Figure 7(a) shows the PL spectra for the Si(1 0 0) substrate and PbS nanostructured thin films on a Si(1 0 0) substrate at an excitation wavelength of 335 nm.…”
Section: Photoluminescencementioning
confidence: 99%
See 1 more Smart Citation